Synthesis and Photoluminescence Behavior of the Eu3+ Ions as a Nanocoating over a Silica Stober Matrix - Rosa, Ieda L. V.; Oliveira, Larissa H.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Springer/plenum Publishers, 2011)
In this work, a SiO2 spherical were prepared by the Stober Method and then recovered with a single layer of Eu2O3 oxide (SiO2@Eu2O3) obtained by the Polymeric Precursor Method. The SiO2@Eu2O3 powder was heated treated at 100, 300, 400, 500 and 800 A degrees C. The samples were characterized by the Scanning Electonic Microscopy (SEM), Thermal Analysis (TGA/DTA), and the luminescent properties of the SiO2@Eu2O3 powders were studied by their emission and excitation spectra as well as by the lifetime measurements of the Eu3+ D-5(0) -> aEuro parts per thousand F-7(2) transition. The SEM analysis shows that the silica prepared by the Stober Method is spherical with a particle size of 460 nm. The emission spectra of the SiO2@Eu2O3 powders presented the Eu3+ characteristics bands related to the D-5(0) -> aEuro parts per thousand F-7(J) (J = 0, 1, 2, 3, 4) transitions at 577, 591, 616, 649 and 695 nm, respectively. The band related to the D-5(0) -> aEuro parts per thousand F-7(2) transition is the most intense in the spectra, and its intensity decreases with the temperature enhancement. The decay curves of the SiO2@Eu2O3 samples presented monoexponential features, and the obtained lifetime values were higher than the Eu2O3 oxide. It was possible to conclude that the D-5(0) -> aEuro parts per thousand F-7(2) hypersensitive transition is strongly dependent on the Eu3+ surrounding.
Keywords: Europium; Luminescence; SiO2; Nanocoating; Photoluminescence properties